2020
DOI: 10.1007/s11420-019-09737-4
|View full text |Cite
|
Sign up to set email alerts
|

Interbody Fusions in the Lumbar Spine: A Review

Abstract: Background Lumbar interbody fusion is among the most common types of spinal surgery performed. Over time, the term has evolved to encompass a number of different approaches to the intervertebral space, as well as differing implant materials. Questions remain over which approaches and materials are best for achieving fusion and restoring disc height. Questions/Purposes We reviewed the literature on the advantages and disadvantages of various methods and devices used to achieve and augment fusion between the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 75 publications
(88 reference statements)
0
46
1
Order By: Relevance
“…lumbar interbody fusion (OLIF) technique has been developed and used to compensate for the shortcomings of the LIF technique. In the case of OLIF surgery, direct correction can be performed on the anterior column of the spine while preserving the psoas muscle, thus protecting the anterior and posterior muscles of the vertebral body [59].…”
Section: A B C D E Fmentioning
confidence: 99%
“…lumbar interbody fusion (OLIF) technique has been developed and used to compensate for the shortcomings of the LIF technique. In the case of OLIF surgery, direct correction can be performed on the anterior column of the spine while preserving the psoas muscle, thus protecting the anterior and posterior muscles of the vertebral body [59].…”
Section: A B C D E Fmentioning
confidence: 99%
“…Lateral-access cage insertion techniques via the retroperitoneal space have been invented to reduce the problems related to TLIF procedures, including lateral lumbar interbody fusion (LLIF) or oblique lateral interbody fusion (OLIF) [ 2 , 4 , 7 , 11 , 12 , 13 , 14 , 15 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. LLIF is conducted via the intermuscular approach dissecting the psoas muscle; thus, it can cause psoas muscle-related complications, including anterior thigh pain, leg weakness, nerve root injury, and others [ 2 , 4 , 11 , 13 , 14 , 25 , 29 ]. To overcome the problems of LLIF, the OLIF procedure has been recently developed.…”
Section: Introductionmentioning
confidence: 99%
“…The OLIF procedure is conducted in the space between the abdominal aorta and psoas muscle, so the risk of psoas muscle injury could be reduced. In addition, several studies have demonstrated that the OLIF procedure provides better outcomes and lower complications than the LLIF procedure [ 2 , 4 , 5 , 11 , 14 , 27 , 29 , 30 , 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Furthermore, the ability to place a large interbody cage to restore disc height and achieve indirect central and foraminal decompression without direct visualization of the neural elements spares the morbidity and complication profile of the posterior approach. [12][13][14][15][16][17][18] However, due to the possibility of approach-related complications including lumbosacral plexus injury, intraoperative radiographic guidance and neuromonitoring are of paramount importance. [19][20][21] Although fluoroscopy has been the mainstay for intraoperative radiographic guidance during LLIF procedures, 3D intraoperative navigation (ION) is being increasingly considered as it may provide for potentially increased accuracy of interbody placement and decreased radiation exposure to operating room staff.…”
Section: Introductionmentioning
confidence: 99%